HERITAGE AS A SOCIAL CONSTRUCTION. A PROPOSAL FOR THE STUDY OF ARCHITECTURAL AND URBAN HERITAGE FROM THE SOCIAL REPRESENTATIONS - Malavassi Aguilar, Rosa Elena (2016)
The present article presents a proposal of a theoretical-methodological framework for the study of architectural and urban heritage that include the official construction of heritage and the daily construction of the same, for this reason the notion of social construction of heritage is proposed approach. The social construction of heritage is analysed from the Theory of Social Representations. Methodological tools to develop this analysis are the Critical Discourse Analysis and Urban Imaginary. The text is divided into three sections. The first presents a theoretical reflection on the concept of heritage and its social construction with an approach from the social representations, the second section presents the application of Critical Discourse Analysis to the study of heritage, the third section deals with the Urban Imaginary around heritage.